Thinking from things : essays in the philosophy of archaeology - Wylie, Alison (University of California Press, 2002)
In this long-awaited compendium of new and newly revised essays, Alison Wylie explores how archaeologists know what they know. Examining the history and methodology of Anglo-American archaeology, Wylie puts the tumultuous debates of the last thirty years in historical and philosophical perspective.